Pengaruh Motivasi, Disiplin Kerja dan Kemampuan Kerja terhadap Kualitas Pelayanan : Studi pada BUMDes Desa Kedungudi Kecamatan Trawas Kabupaten Mojokerto - Bidang Bank Sampah - Muhammad Rafli Novalita Fathrul Putra; Hartono Hartono; Agoes Hadi Poernomo (Jurnal Visi Manajemen, 2025)
This study was conducted to analyze the influence of motivation, work discipline, and work ability on service quality at the Village-Owned Enterprise (BUMDes) in Kedungudi Village, Trawas District, Mojokerto Regency. The background of the study stems from the important role of human resources in supporting the quality of public services, especially in the Waste Bank business unit managed by the BUMDes. Human resources are considered the most strategic asset in achieving organizational goals, especially in community-based enterprises such as village-owned enterprises. The study used a quantitative approach with a survey method. The research sample was all 25 BUMDes employees and was determined using a saturated sampling technique. The research instrument was a questionnaire with a Likert scale that had undergone validity and reliability tests. The use of a Likert scale questionnaire ensures measurable perceptions and attitudes from respondents regarding the studied variables. Data analysis was conducted through multiple linear regression with the assistance of SPSS software. The results showed that partially, work discipline and work ability had a significant positive effect on service quality, while motivation had a significant negative effect. This finding indicates that motivation, if not aligned with organizational needs, may lead to counterproductive outcomes. Simultaneous testing showed that all three variables significantly influenced service quality, with a coefficient of determination of 68.8%. In other words, nearly 70 percent of service quality can be explained by motivation, work discipline, and work ability. This finding underscores the importance of holistic human resource management, encompassing strengthening work discipline, improving competency, and reviewing the motivation system to align with both organizational and individual needs. Research recommendations include evaluating the motivational models used, consistently monitoring discipline, and providing ongoing training. Continuous training and development programs are essential to sustaining and improving service quality in the Kedungudi Village-Owned Enterprise (BUMDes).